วิถีชุมชนคนเลี้ยงวัว จังหวัดสุราษฎร์ธานี: กรณีศึกษา อาเภอพระแสง และอาเภอเวียงสระจังหวัดสุราษฎร์ธานี - ศรีสมโภชน์, สมกมล (Thai Interdisciplinary and Sustainability Review, 2019)
The research findings were summarised as follows: A good bull’s traits should comprise of small ears and eyes, hanged tail, bushy genital hair, thick eyebrows, short face, big horns, testicles lifting forward, and especially the big across chest with taper buttocks like that of a lion. The people pampered the bulls by taking them to a walk “in the sun” in the morning and evening, gave them intensive and continuous training, nourished them with good food, raised them in an “untouchable by bugs and mosquitoes” manner and often brought superstitious methods “to boost morale” among themselves and “to terrorise” their opponents. In cowboys’ lives, they must treat the bulls like family members, and the bulls were often treated better than their family members, but the sons and wives accepted these conditions because they thought of the bulls as "life partners" to them as well. A bull rider must be fearless and have the spirit of gambling in the heart, especially for the people who would rise themselves up to be a “head” or a “King” must be rugged, determined, extravagant, daring, and trustworthy, have pride in their honour and dignity, enough to use a vigilante system to handle problems without fear of any law. Although health officials looked at the lifestyle of cowboys as dirty and the moralists deemed it as animal cruelty, but, on the other side of bull fighting activities, there were many business networks all over and these was engraved into the southerner’s way of life for a very long time and deeply rooted in their kinships. Getting rid of such lifestyle was not simple because a player must be tough, brave, independent, eager to lead, daring, among other things, which clearly reflected the inborn characteristics of a southerner.